Consequences of alcohol consumption among women cared for in a Psychosocial Care Center - Pillon, Sandra Cristina (2014)
The aim of this study was to identify the consumption of alcohol and its impact on the physical, interpersonal, and intrapersonal realms, as well on the impulse control and social responsibility of a group of women receiving specialized treatment. It is a descriptive qualitative study. The sample comprised 61 women, predominately adults, single, with low education levels and who were domestic workers. On average they consumed high quantities of distilled alcohol per day. The women were diagnosed with alcohol dependence syndrome and presented significant damages to their intrapersonal and impulse control areas. A minority sought treatment to stop drinking, and 59% had initiated a prior treatment for mental and psychiatric disorders. The results provided use with information on alcohol consumption, as well as on the consequences of drinking among women. Such data is essential for rethinking how to plan health care proposals for this population. doi: 10.5216/ree.v16i2.22712.